An evaluation framework for low performers and human resource management planning: Application to a life insurance company in Korea - Park, Bong Je; Park, Min Jae; Shin, Je Goo (Evaluation and Program Planning, 2024)
This study comprehensively explores the factors that lead to low performers in an organization. A thorough literature review was conducted to construct an interview guide and obtain classification criteria for the factors that lead to low performers. Managers and low performers at multiple firms were interviewed individually to understand the various phenomena related to low performers in organizations. Based on the content of these interviews, 12 factors, classified into individual, leader, work, and organizational dimensions, were identified after three rounds of revisions by business administration experts. Next, a case study of Korea's S Life Insurance Company was conducted to examine the practical implications of the factors that contribute to creating low performers. In this case study, the analytic hierarchy process (AHP), involving eight departmental heads S Life Insurance Company's HR division, was utilized to identify the main factors that must be considered when evaluating low performers. While previous studies have examined low performers either at the individual, organizational, or institutional levels, this study presents a comprehensive and integrated evaluation framework of the factors that cause low performers. The proposed framework facilitates the identification and evaluation of low performers in various organizations and industries, and thus has practical implications in terms of establishing strategies to manage low performers more efficiently and improve organizational performance.
Keywords: Efficiency, Organizational; Employee Performance Appraisal; Humans; Insurance, Life; Interviews as Topic; Leadership; Organizational Case Studies; Personnel Management; Program Evaluation; Republic of Korea; Analytic Hierarchy Process; CSFs; Delphi Method; Education; Evaluation Framework; Low Performers